Comparative Study of Topsis and Fuzzy Topsis for the Determination of Water Allocation in an Urbanized River Basin - Wei Koon, Lee (Journal of Advanced Research Design, 2025)
The water allocation decision-making model developed by Lee et al. (2023a, 2023b) provides a robust framework that integrates economic, social, and environmental factors with basin water availability to prioritize water allocation. However, the model’s reliance on extensive data collection poses significant challenges in data-scarce regions. To mitigate this issue, this study proposes an alternative using a fuzzy TOPSIS algorithm, designed to yield similar outcomes while requiring less data. A comparative analysis between the traditional TOPSIS and fuzzy TOPSIS methods demonstrates analogous trends, with both identifying Option 1 as optimal despite minor ranking differences. Fuzzy TOPSIS stands out for its ability to handle imprecise data, simplifying the evaluation process in uncertain contexts. Nonetheless, its success depends on the strategic perspective of decision-makers. This research underscores the necessity for ongoing refinement and evaluation of the models to effectively tackle uncertainties in water resource management. The enhanced model significantly advances water governance by promoting transparency, stakeholder inclusivity, and informed decision-making. By incorporating multiple criteria and stakeholder perspectives, it fosters equitable and efficient water resource utilization. Ultimately, the model contributes to a more sustainable and resilient future for societies and the environment.